Learning System with Digital Literacy Based on Guided Inquiry Integrated Flipped Classroom Using Discord Application on Colloid - Handri, Silvi; Mawardi, Mawardi; Aini, Syamsi; Nizar, Umar Kalmar (Postgraduate, University of Mataram, 2023)
This research aims to produce an integrated flipped classroom learning system based on guided inquiry using Discord application on colloid material for first year students using the Plomp development model developed by Tjeerd Plomp. The research instrument used a validation sheet filled in by 5 UNP chemistry lecturers, an interview sheet for assessment at the one-to-one evaluation stage which contained several questions with answers in the form of explanations from 3 students, a practicality sheet filled out by 9 students then content validity and constructs were analyzed using Aiken's V scale, and practicality was analyzed using practical percent. The results of the analysis of the content and construct validity data obtained were stated to be valid with a value of V = 0.84 and 0.91, as well as the results of the practicality test data analysis obtained a P value (%) of 93 in the very practical category. So that an integrated learning system is produced, flipped classroom based on guided inquiry using the Discord application on colloidal material which is used as an alternative method in the learning process in lectures.